Kedudukan Keterangan Ahli di Sidang Pengadilan dalam Pembuktian Perkara Korupsi - Novrianto, M.; Indrajaya, Indrajaya (Universitas Batanghari Jambi, 2024)
Corruption is an extraordinary crime that has an impact on the nation's economy. In general, corruption is carried out by educated people who have wide networks in society. When examining corruption cases in court, the presence of experts can assist the judge in proving the defendant's guilt. Expert testimony as evidence has important power in making clear a criminal act. The judge decides that a person has indeed committed a criminal act determined by at least two valid pieces of evidence and he is convinced that a crime has indeed occurred. This research is to find out the position of expert testimony in proving criminal acts of corruption, the research method used is normative research.